Analysis Of Determining The Cost Of Goods Produced Based On Job Order Costing At Eleven Sport Printing Business In Bengkulu City - Hutabarat, Kristia Elsa Yohana; Anggriani, Ida; Astuty, Kamelia (Journal of Management, Economic, and Accounting, 2025)
This study discusses the use of the Job Order Costing method to calculate the cost of goods produced and determine the selling price of products at the Eleven Sport printing business in Bengkulu City. Job Order Costing records production costs specifically for each product, allowing for more accurate calculations. This research uses a quantitative descriptive method with primary data collected through interviews and documentation. The analysis was conducted for the period January-June 2024, with the results showing the total production cost of Rp 724,181,003 and the cost of production per jersey stel is Rp 66,469. Currently, Eleven Sport determines the selling price of Rp 120,000 per suit without a specific calculation method, only based on estimates. However, with the Job Order Costing method, a more accurate selling price is suggested at Rp 86,410 per suit. This difference of Rp 33,590 shows that the application of this method not only helps in setting a more precise cost of goods produced, but also in determining a selling price that is in line with the company's profit target. The results show the importance of Job Order Costing to improve the